Pemikiran Fikih Muhammad Ibn Isma’il al-Bukhary ‎(Bagian Kedua)‎ - Muh. Fathoni Hasyim (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
Al-Bukhary is a person with expertise in various areas of Islamic science. He is expert on the Qur’anic exegesis, Prophet tradition, jurisprudence, theology, history, belle lettre, and so on with high level of achievement, especially on prophet tradition and jurisprudence. He has a consistent viewpoint even more persistence than Ahmad ibn Hanbal who is well-known for his insistence in employing only sound prophet tradition in jurisprudence. Al-Bukhary never uses weak tradition in jurisprudence. He also devises for his own so very distinct five methods of ijtihad that his jurisprudential interpretation is so distinct compared to other jurists of his time. This article presents al-Bukhary as an absolute jurist (mujtahid mutlaq), focusing on the structure of his legal theory. Therefore, two aspects will be discussed; his methodological structure which makes him worthy of the title; and its application in his jurisprudential products.